Chromosome‐level reference genome assembly and gene editing of the dead‐leaf butterfly Kallima inachus. (10th June 2020) - Yang, Jie; Wan, Wenting; Xie, Meng; Mao, Junlai; Dong, Zhiwei; Lu, Sihan; He, Jinwu; Xie, Feiang; Liu, Guichun; Dai, Xuelei; Chang, Zhou; Zhao, Ruoping; et al.
Abstract: The leaf resemblance of Kallima (Nymphalidae) butterflies is an important ecological adaptive mechanism that increases their survival. However, the genetic mechanism underlying ecological adaptation remains unclear owing to a dearth of genomic information. Here, we determined the karyotype ( n = 31) of the dead‐leaf butterfly Kallima inachus, and generated a high‐quality, chromosome‐level assembly (568.92 Mb; contig N50: 19.20 Mb). We also identified candidate Z and W chromosomes. To our knowledge, this is the first study to report on these aspects of this species. In the assembled genome, 15, 309 protein‐coding genes and 49.86% repeat elements were annotated. Phylogenetic analysis showed that K. inachus diverged from Melitaea cinxia (no leaf resemblance), both of which are in Nymphalinae, around 40 million years ago. Demographic analysis indicated that the effective population size of K. inachus decreased during the last interglacial period in the Pleistocene. The wings of adults with the pigmentary gene ebony knocked out using CRISPR/Cas9 showed phenotypes in which the orange dorsal region and entire ventral surface darkened, suggesting its vital role in the ecological adaption of dead‐leaf butterflies. Our results provide important genome resources for investigating the genetic mechanism underlying protective resemblance in dead‐leaf butterflies and insights into the molecular basis of protective coloration.